Transformation of Elementary Science Education through the RADEC Model and Digital Learning Based on Augmented Reality for Human Digestive System - Kirana, Cut Rania; Sopandi, Wahyu; Sujana, Atep; Febrialita Salma Dwinandha Putri (International Journal of Elementary Education, 2025)
Science learning in elementary schools is still dominated by conventional methods that do not involve students actively, especially in understanding the material of the human digestive system. Limited teaching aids and lack of technology integration are challenges in creating interesting and effective learning. This study aims to analyze the needs and design the development of digital teaching materials based on the RADEC model assisted by Augmented Reality (AR) technology to improve conceptual understanding and active participation of students. This research uses a quantitative descriptive method with a survey design. The research subjects consisted of 41 fifth grade students and three fifth grade teachers. Data were collected through observations, interviews, and questionnaires using instruments such as observation sheets, interview guidelines, and questionnaires. The data were analyzed using quantitative descriptive analysis techniques. The results showed that respondents stated that they needed interactive digital teaching materials based on RADEC and AR. Learning in the classroom is still teacher-centered, minimal technology integration, and limited teaching aids, so it is not optimal in encouraging active student involvement. The conclusion of this study confirms the need for innovative digital teaching materials to overcome the limitations of conventional methods and improve the quality of science learning. The implication of this research is the importance of developing RADEC and AR-based teaching materials to support students' motivation, conceptual understanding, and critical thinking skills.